A facile and green pretreatment method for nonionic total organic halogen (NTOX) analysis in water – Step II. Using photolysis to convert NTOX completely into halides. (15th November 2018) - Bu, Yinan; Song, Mingrui; Han, Jiarui; Zhang, Zhenxuan; Chen, Baiyang; Zhang, Xiangru; Yang, Mengting
Abstract: Adsorbable organic halogen (AOX) is a parameter conventionally used to indicate the sum of organic halogenated disinfection byproducts (DBPs), which are formed from the reactions of disinfectants with dissolved organic matter, bromide and iodide in water. To overcome the issues of the AOX analytical method, we proposed a new facile and green pretreatment method to enable the analysis of nonionic total organic halogen (NTOX) via the following three steps: 1) separation of NTOX and halides with electrodialysis, 2) conversion of NTOX with ultraviolet (UV) photolysis, and 3) analysis of halides with ion chromatography. To verify this proposal, we mainly evaluated the efficiency of vacuum ultraviolet (VUV) coupled with UV photolysis (VUV−UV) in converting NTOX into halides. Results showed that by applying VUV irradiation for 60 min and UV irradiation at pH 10–11 for another 30 min, over 85.5% of each halide from 20 representative small molecular weight DBPs (each at 100 μg-X/L level) was recovered. The purpose of UV photolysis under alkaline conditions was to reduce oxyhalides (such as bromate and iodate) formed in the VUV process back to halides. With the aid of electrospray ionization-triple quadrupole mass spectrometry, we captured the whole pictures of high molecular weight polar DBPs in a chlorinated drinking water before and after VUV−UV, through which averagely 96.4% of dehalogenation with the VUV−UV treatment was observed. An illustrative comparison of the conventional AOX method and the proposed NTOX method indicates that although the detected NTOX was lower (by 2.3–30.6%) than AOX, the results of the two methods were highly correlated (R 2 > 0.97). All these hence verified the photolysis as a mature yet novel tool for sample pretreatment in environmental analytical chemistry. Graphical abstract: Image 1 Highlights: A new three-step method was proposed to detect nonionic total organic halogen (NTOX). The ability of UV photolysis in converting NTOX into halides was evaluated and optimized. The recoveries of 20 small MW model compounds by photolysis were ≥85.5%. The average recovery of an array of high MW compounds by photolysis was 96.4%.